In Vitro Assay of Translation Inhibition by Trichothecenes Using a Commercially Available System - Takahito Toyotome; Katsuhiko Kamei (Toxins, 2021)
Trichothecenes are a family of major secondary metabolites produced by some common filamentous fungi, including plant pathogenic and entomopathogenic fungi. It may be considered difficult to conduct a comparison between the toxicities of trichothecenes with consideration of different conditions and cell lines. In the current study, we developed an in vitro assay based on a commercially available system to estimate the translation inhibition, that is, the main toxicity, of trichothecenes. The assay was applied to estimate the inhibition of protein synthesis by trichothecenes. Initially, we examined the assay using trichothecene dissolved in water followed by an assessment of trichothecene solutions dissolved in acetonitrile. The obtained data showed that the assay tolerated the small amount of acetonitrile. The assay examined in this study has the advantages of a short operation time (one day), ease of use, and data stability, as it is a non-cell-based assay whose components are commercially available. It is expected that this assay will contribute to the evaluation of the toxicity of a vast number of trichothecenes.